Bioelectrochemical Behavior Of Wild Type Bacillus Cereus In Dual Chamber Microbial Fuel Cell - Islam, M. Amirul; Woon, Chee Wai; Ethiraj, Baranitharan; Yousuf, Abu; Huei, Ruey Ong; Khan, Maksudur R. (IIUM, 2017)
A microbial fuel cell (MFC) is a bioelectrochemical system that uses living microbes as biocatalyst to oxidize organic substrates as well as release electrons that can be harvested in an external circuit to produce electrical energy. In this study, a proteolytic biocatalyst, Bacillus cereus, has been employed for the first time in a microbial fuel cell (MFC). The wild type pure culture was isolated from municipal wastewater and identified using Biolog Gen III analysis. The MFCs were fueled with palm oil mill effluent (POME) and attained a maximum power density of about 3.88W/m3. The electrochemical behavior of the MFC was evaluated using a polarizationcurve, electrochemical impedance spectroscopy (EIS), and cyclic voltammetery (CV) analysis. The CV and EIS results suggest that the predominant electron transfer occurred through the electron shuttle mechanism. The electron shuttle mediators excreted by B. cereus significantly reduced the anode charge transfer resistance (52.95%). The FESEM result shows that B. cereus has the capability to form an effective biofilm on the anode electrode surface. These results revealed the electrocatalytic potentiality of B. cereus, making it a promising candidate to be used in MFCs. Therefore, this biocatalyst can be used to generate electricity through wastewater valorization.